FROM THE EDITOR - Lategan, Bernard C. (Scriptura, 1983)
What is the relevance of the Bible for vital issues in contemporary society? This question has acquired a note of urgency in the present context in which we find ourselves. If it is claimed - and rightly so - that the Bible has to do with all aspects of man’s existence, the scientific study of these documents cannot take place in abstracto. The implications of fundamental biblical concepts for the central issues in our society need to be thought through and spelt out in concrete terms. Biblical Studies cannot keep itself aloof from contemporary ethical problems, but should accept the task to make a responsible and considered contribution to the debate.